Izboljšanje pretoka dela v kompleksnem projektu - Volgemut, Tadej (OTS 2026 Sodobne informacijske tehnologije in storitve: Zbornik 29. konference, 2026)
On a complex project in a regulated environment, we initially focused primarily on the work of individuals: how to increase their efficiency and get more done in a sprint. However, frequent requirements changes, limited test environments, infrequent deployments, and waiting between individual steps continued to reduce the predictability of delivery. Over time, we realized that the main problem was not the speed of individual work, but the flow of work through the entire system. In this article, we present how we identified bottlenecks, why more people did not necessarily mean faster execution, and how we kept Scrum as a framework, but began to review and align ongoing work with some elements of the Kanban approach. We especially emphasize the role of QA in connecting teams and shortening the path to feedback. We do not present a final solution, but rather the changes implemented, their first effects, practical limitations, and improvements that we have not yet managed to implement.